INDIVIDUAL AND COMBINED EFFECTS OF HEAVY METALS ON BEHAVIOUR AND RESPIRATORY RESPONSES OF OREOCHROMIS MOSSAMBICUS - James, R (Indian Journal of Fisheries, 2011)
Sublethal effects of Copper, Zinc and Cadmium on behaviour and respiratory responses of Oreochromis mossambicus were studicid individually and in combinations. Animals exposed to Cu + Zn and Cu + Cd combinations exhibited the strange phenomenon of behavioural changes than the animals exposed to Copper or Zinc or Cadmium individually. The rates of oxygen consumption and opercular movements were increased when the fish were exposed to chosen metals individually and in combinations on first day while it was declined on 15th day. The results arc discussed in the light of recent literature.